Cultural adaptation and validation of the short food literacy questionnaire (SFLQ) for adults in Lebanon - Sahar Obeid; Souheil Hallit; Feten Fekih-Romdhane; Marie Hokayem; Ayoub Saeidi; Yonna Sacre; Maha Hoteit (PLoS ONE, 2025)
Introduction In recent decades, Food Literacy (FL) has gained significant attention in the fields of food and nutrition. It is considered a key determinant of public health and presents a promising approach to addressing health challenges like obesity and environmental sustainability. However, Lebanon currently lacks a validated tool to assess food literacy. In this context, the Short Food Literacy Questionnaire (SFLQ) offers potential for translation and cultural adaptation. Adapting an established tool for use in a new cultural setting enables cross-country comparisons and supports the development of cross-cultural study models. Therefore, this study aims to culturally adapt the SFLQ to assess food literacy among Lebanese adults, enhance their knowledge, and promote healthier lifestyle habits. Methods A nationally representative sample of 450 adults was selected through probability cluster sampling from the eight Lebanese governorates. The SFLQ was administered between 11 December 2022 and 23 March 2023 to evaluate participants’ food literacy. Confirmatory Factor Analysis was conducted using SPSS AMOS version 30, applying the maximum likelihood estimation method to obtain parameter estimates. Results The average age of the participants was 46.0 years, with women making up 59.0% of the sample. The one-factor model showed an acceptable fit after accounting for correlated residuals between items 4−5, 9−10 and 11−12 (RMSEA = 0.079 (90% CI 0.068, 0.091), SRMR = 0.053, CFI = 0.935, TLI = 0.916). Internal consistency was satisfactory (ω = .86/ α = .86). Measurement invariance across gender was confirmed at the configural, metric and scalar levels. Males had significantly higher average SFLQ scores than females (32.80 ± 7.91 vs 28.76 ± 9.26; p < 0.001, Cohen’s d = 0.486). A significant negative correlation was observed between SFLQ and Household Food Insecurity Access scores (r = −0.28; p < 0.001). Conclusion The SFLQ demonstrated strong internal consistency, indicating that it is a reliable tool for both research and clinical use. Expanding validation efforts to include a broader Arabic-speaking population, particularly individuals without internet access, would further strengthen the tool’s applicability and cultural relevance across diverse contexts in the Arab world.